PENINGKATAN KAPASITAS PENGELOLA DESTINASI PARIWISATA ALTERNATIF EKOWISATA WAE BOBOK DI LABUAN BAJO - Rostini, Ida Ayu; Kaban, Irna Karina; Rudiyanto, Roseven; Hutagalung, Septian (Universitas Sanata Dharma, 2023)
The Wae Bobok ecotourism destination is one of the alternative tourist attractions around Labuan Bajo, West Manggarai Regency. As an alternative to tourism, the development of the Wae Bobok destination tends to be slow compared to other tourist destinations. One of the main problems is the ability of the local managers to promote the Waebobok destination and the ability to interpret tourist objects in Wae Bobok. Therefore, this community service aim is training in developing the ability to compose narratives by answering 6 question words, namely Apa (what), Siapa (who), Kapan (when), Dimana (where), Mengapa (why), and Bagaimana (how) (5W+1H) and convey interpretation using the role-play method. The results show an improvement in the ability to train participants to compose better Wae Bobok destination narrations by containing 5W+1H elements and improve their ability to interpret Wae Bobok destination narrations.